2016
DOI: 10.1186/s12889-016-2916-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of medical waste management in seven hospitals in Lagos, Nigeria

Abstract: BackgroundMedical waste (MW) can be generated in hospitals, clinics and places where diagnosis and treatment are conducted. The management of these wastes is an issue of great concern and importance in view of potential public health risks associated with such wastes. The study assessed the medical waste management practices in selected hospitals and also determined the impact of Lagos Waste Management Authority (LAWMA) intervention programs. A descriptive cross-sectional survey method was used.MethodsData wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
105
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(159 citation statements)
references
References 19 publications
9
105
3
2
Order By: Relevance
“…4;2017 This finding is comparable to a study done in Lagos where burning of hospital waste was found to be a common practice (Longe & Williams, 2006). It however differed from another study done in seven hospitals in Lagos where all the hospitals employ the services of Lagos Waste Management Authority (LAWMA) for final waste disposal and treatment except one hospital that offered on-site treatment of waste with incinerator (Olufunsho et al, 2016).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…4;2017 This finding is comparable to a study done in Lagos where burning of hospital waste was found to be a common practice (Longe & Williams, 2006). It however differed from another study done in seven hospitals in Lagos where all the hospitals employ the services of Lagos Waste Management Authority (LAWMA) for final waste disposal and treatment except one hospital that offered on-site treatment of waste with incinerator (Olufunsho et al, 2016).…”
Section: Discussionmentioning
confidence: 49%
“…The level of awareness among healthcare workers regarding health care waste has not been adequately documented in Nigeria (Abubakar, 2013;Stephen & Elijah, 2011). Many health facilities in Nigeria do not have a specific policy for management of hospital waste (Olufunsho, Aishat, & Azuka, 2016) The study therefore aims at investigating the knowledge, and health care waste management among health workers in Enugu State, Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…[43], which may contain highly hazardous substances and may impose potential risks to medical staffs, patients and the general public [43]. The reverse logistics of medical waste comprises of three main activities: (1) collection and separation at the sources; (2) transportation to respective facilities; and (3) proper treatment and disposal [44]. At the sources, medical waste is usually collected and sorted with color-coded containers based on their characteristics, but the color selected, the waste classification and the requirement of maximum storage time in different regions are by no means identical [45].…”
Section: Problem Descriptionmentioning
confidence: 99%
“…With the growing concern on medical waste management, some developing countries have recently implemented interventions that have improved their waste management practices (Kumar et al, 2015;Tabash et al, 2016;Awodele et al, 2016). Although, there is very limited information on health care waste management in Cameroon, few studies conducted report medical waste management as a challenge in both primary and tertiary care facilities (Doumtsop, 2014).…”
Section: Introductionmentioning
confidence: 99%